Pengaruh Insulin, Jahe dan Kombinasi Keduanya Terhadap Jumlah Sel Trofoblas Rattus Norvegicus Model Diabetes Pragestasional - Alif Zahrotin (Qanun Medika - Jurnal Kedokteran FK UMSurabaya, 2018)
Diabetes mellitus (DM) is a metabolic disease with characteristics of hyperglycemia that has an effect on increasing morbidity and mortality in the mother. One of the complications of pregestational DM (pGDM) is preeclampsia (PE). The perinatal mortality rate increases 20x in pGDM women with PE complication. Exposure to hyperglycemia causes an increase in oxidative stress that increases apoptosis of trophoblast cells which in turn causes the decrease of proliferation and the number of trophoblastic cells and leads to endothelial dysfunction and hypoxia. The purpose of this study was to distinguish the effect of insulin administration and ginger extract on the number of trophoblast cells of R. norvegicus. This research was an experimental research using post-test only control group design. The population used were pregnant R. norvegicus. The sampling technique was simple random sampling with independent variables are insulin and Z. officinale extract and the dependent variable is the number of trophoblast cells. Data analysis of the number of trophoblast cells used wereKruskal-Wallis and Mann-Whitney test. The result showed that there was a significant difference in the trophoblast cell number with p-value <0,05 (p = 0,001) on positive control with insulin treatment group. The conclusion of this study was the presence of ginger extract can be used as a single therapy or combination with insulin for pregestational diabetes.